Isolated Word Lateral Phonetic Class Speech Recognition in Malayalam Language - Kurian, Cini (International Journal of Computer Sciences and Engineering, 2025)
For Speech recognition in the selection of text corpus commonly some phonemes will never likely to occur and the words which includes such phonemes will never be recognized properly. Therefore special care to be taken to include all phonemes of a language in maximum word positions( Start, end , middle). Our aim in this paper is to develop a speech recognizer for lateral class of words of Malayalam Language.